Cross Product Pada Vektor Tegak Lurus Dengan Vektor Asal - Anggi Virlanda; Rizka Fadila; Rindiani Rindiani; Rendi Fitrah Handoko; Septyara Sinaga; Hesti Al Duma (Journal of Student Development Information System (JoSDIS), 2026)
The cross product is an operation with geometric characteristics. This study aims to analyze the orthogonality of the cross product of two vectors and its relationship to the original plane. Based on the basic principles of vectors, the cross product of two vectors a and b produces a new vector perpendicular to the plane formed by the two original vectors. This resulting vector is determined by the equation |a × b| = |a| |b| sin⁡θ. The method used is a literature study. The results of the discussion indicate that the perpendicularity property is crucial to the direction and magnitude of the cross product.